Penguatan Karakter dan Jati Diri Bangsa Melalui Implementasi Nilai Asta Cita Berbasis Kearifan Lokal Desa Rejuno Kecamatan Karangjati Kabupaten Ngawi Jawa Timur - Bambang Sigit Widodo; Silkania Swarizona; Iman Pasu Marganda Hadiarto Purba; Jauhar Wahyuni; Dina Rahmawati (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This Community Service Program (PKM) was designed to strengthen national character and identity through the application of Asta Cita values among the residents of Rejuno Village, Karangjati District, Ngawi Regency, East Java. Conducted over two days, the program involved active participation from youth groups, community leaders, and village officials. The activities consisted of the introduction of national and civic values, interactive discussions with local figures, and group reflections aimed at formulating social commitments rooted in the Asta Cita principles. The findings show a notable increase in participants’ understanding and appreciation of the eight core values: patriotism, mutual cooperation, honesty, responsibility, hard work, discipline, tolerance, and social justice. Moreover, local wisdom and traditions—such as martial arts practices and community deliberations—were revitalized as effective tools for embedding these values within daily life. This program highlights that national character building does not solely rely on formal education or governmental initiatives but can also grow organically from community-based cultural practices. By integrating local heritage with national ideals, the PKM successfully promoted a sense of unity, civic awareness, and moral responsibility among the people of Rejuno Village, illustrating how local culture can serve as a strong foundation for fostering national identity and integrity.